Combatividade, participação e cidadania: as metamorfoses da Central Única dos Trabalhadores - Toledo, Cleber José de (2013)
This work is based on the political position changes of the unionists from Central Única dos Trabalhadores, from its begin in in 1983 until it has been recognized as citizen unionism activist in the nineties, more exactly since its V Congress in 1994. We will try to demonstrate all the process made by the Central and its metamorphoses, more specific the transformation of production, economy, politics and society that will really changes its political strategy in the union fight. Starting with a careful analysis of a consolidated bibliography, as well as the investigation of the congress resolutions that guided Central position s during the investigated period and the results of an interview made with Vicente Paulo da Silva (Vicentinho), a present Federal Representative, which is so important to reach the goal of this work. This way we will try to show the reader a study of internal and external causes that influenced Central s position during a very long period of its history, always trying to learn the totality of transformation process